If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(3 + y) = -12 (3 * -6 + y * -6) = -12 (-18 + -6y) = -12 Solving -18 + -6y = -12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -6y = -12 + 18 Combine like terms: -18 + 18 = 0 0 + -6y = -12 + 18 -6y = -12 + 18 Combine like terms: -12 + 18 = 6 -6y = 6 Divide each side by '-6'. y = -1 Simplifying y = -1
| ln(4x)= | | x+24=4x-30 | | 0=5(r^2+4)-30r | | 2(r-4)=4r | | x(x+2)(x+4)=105 | | n+2=-4 | | x(x-2)(x+4)=105 | | 2x+6x+6=10 | | 3ab+5cd+6ab= | | 23-2x+-5=-6 | | f(t)=4r-10 | | x^2-21x+6=5x+6 | | 4a^2+4ab+b^2=0 | | X^2+10X-15=5x+19 | | -7(t-2)-(t+3)=6 | | 9t^2-30t+25=0 | | 7x-2(x+4)=6+5(x+7) | | 3c^2+27c-66=0 | | 4k+3.6=7.8 | | 12m^2-48=0 | | 16x-57 = 10x+3 | | 0.50x+.75y=11.50 | | -4(x+6)=-8 | | x^2-3x+2=-9x-3 | | 4+10= | | 16m+4n-6m+11n= | | 3-6y+5=2y+14-6y | | 50000=312.50x | | 50000=27750+200x | | 3(x+2)=4p-10 | | Y=3000*9.25+2*7.25*8x+2*5.25*8x | | (2-7x)+(100-10x)=(90-20x) |